The importance of entrepreneurial education in developing a culture of creativity and innovation among university students (Entrepreneurship Journal for Finance and Business, 2025)
Entrepreneurial education is currently a fundamental requirement for developing students' abilities and talents, equipping them with academic and practical skills and expertise, and preparing them to keep pace with emerging developments by fostering a culture of entrepreneurship toward creativity and innovation.                                                                       The current study aims to demonstrate the importance of universities' orientation towards formulating entrepreneurial educational goals and programs for the purpose of developing creativity and innovation by supporting the spirit of entrepreneurial culture among students and encouraging competition to discover entrepreneurs and innovators by encouraging and developing entrepreneurship programs in university educational institutions. The research relies on the use of the descriptive analytical approach and the pursuit of benefiting from international experiences in this field to formulate educational goals towards developing a culture of creativity and innovation Directing the university's vision and mission and transforming them into successful entrepreneurial practices by linking education to practical reality so that the university can play a pioneering role that influences society by preparing graduates who carry a culture of creativity and innovation to achieve sustainable development goals. One of the most important results of the research is the need to direct university policies towards preparing educational programs that enhance the skills of creative students, and encourage students to generate entrepreneurial ideas and transform them into entrepreneurial projects to achieve sustainable development goals and reduce poverty and unemployment.